The misuse of antiretrovirals to boost pig and poultry productivity in Uganda and potential implications for public health - Ndoboli, Dickson; Ng'ang'a, Fredrick M.; Lukuyu, Ben A.; Wieland, Barbara; Grace, Delia; Braun, A. von; Roesel, Kristina (Veterinary World, 2021)
Background and Aim: Since 2015, local newspapers reported that pig and poultry farmers in Uganda use antiretroviral drugs (ARVs) to promote growth in animals and control diseases. This study was conducted to assess farmers’ knowledge, attitude and perceptions about the use of antiretroviral drugs as boosters in pigs and poultry and the possibility of detecting the antiretroviral drugs in meat using available laboratory methods. Materials and Methods: In 2019, a cross-sectional study was conducted in ten districts in Uganda. In 20 focus group discussions with 100 pig and poultry farmers and 70 animal health service providers, we assessed the use of ARV in livestock enterprises. Subsequently, samples of chicken, pigs, and animal feeds were collected from volunteer participants, and screened for residues of saquinavir, lopinavir, nevirapine, and efavirenz using liquid chromatography-tandem mass spectrophotometer. Results: Participants in all ten districts were predominantly smallholder farmers supplying the local markets. All groups reported the use of ARVs in pigs and broiler birds but not in layer hens. In the absence of good quality feeds, the motivation for feeding ARVs was rapid animal weight gain, as well as the control of animal diseases, for which farmers have no alternative solutions. ARVs were obtained within the community for free, against cash, or in-kind payment. Residues of lopinavir were detected in four, and saquinavir in seven districts, and all three sample matrices. Conclusion: Our study findings confirm anecdotal news reports on ARV use in livestock. While our findings are not generalizable to the whole country, they call for a representative follow-up. As the drugs were detected in tissues destined for human consumption, the potential risk to human health warrants further investigation.